The programmer life-cycle. - Ovans, Russell (Software engineering notes.)
The traditional analysis of programmer productivity ignores the reality that work rates of programmers are variable over time. Not unlike the software systems they construct, programmers follow a predictable life-cycle. However, the programmer life-cycle is not comprised of activities but rather by phases that directly affect and predict productivity. The sequence of phases is: euphoric, productive, irreplaceable, resentful, bored, and unproductive. Overall productivity is characterized by an initial six month period of intense interest, at which time productivity rates are often an order of magnitude higher than the oft-quoted 500 LOC/month average. After a short period of volatility, the programmer then enters a prolonged phase of steadily dwindling interest, resulting in productivity rates that mimic the average. Each time a programmer switches employers or begins a significantly new project, the life-cycle starts anew.